Two novel sequence variants in MSH2 gene in a patient who underwent cancer genetic counseling for a very early-onset epithelial ovarian cancer. Issue 1 (December 2016) - Pensabene, Matilde; Condello, Caterina; Carlomagno, Chiara; De Placido, Sabino; Liccardo, Raffaella; Duraturo, Francesca
Abstract Background Early-onset or hereditary ovarian cancer is mostly associated withBRCA1 orBRCA2 mutations. Mismatch repair genes sequence alteration frequently cause colorectal cancer, and, in less extent, other tumors, such as ovarian cancer. Subjects with personal and/or family history suggestive for hereditary cancer should be addressed to cancer genetic counseling, aimed to the identification, definition and management of hereditary cancer syndrome, by a multidisciplinary approach. Case presentation A woman with a very early onset epithelial ovarian cancer underwent to cancer genetic counseling and genetic testing. Pedigree analysis suggested a clinical diagnosis of Lynch II syndrome, according to the Amsterdam criteria. The MMRpro model showed a cumulative risk of mutation of 50.3 %, thus, genetic testing was offered to the patient. Two germ-line mutations have been identified in exon 11 ofMSH2 gene: c.1706A > T (p.Glu569Val) and c.1711G > T (p.Glu571*). Both DNA alterations were novel mutations not yet described in literature. The first is a missense mutation that is to be considered an unclassified variant; the second is nonsense mutation that created a premature stop codon resulting in a truncated not functioning protein. Both genetic alterations were found in the patients' father DNA. Conclusions The present report finds out two unpublished sequence alterations in exon 11 of theMSH2 gene, one on which can be considered causative of Lynch phenotype. Moreover, it stresses the importance of the multidisciplinary onco-genetic counselling in order to correctly frame the hereditary syndrome, suggest the right genetic test, and offer the most appropriate management of the cancer risk for the patients and her family members.